Targeting Hepatic Glycerolipid Synthesis and Turnover to Treat Fatty Liver Disease. (10th April 2014) - Schweitzer, George G.; Finck, Brian N.
Abstract : Nonalcoholic fatty liver disease (NAFLD) encompasses a spectrum of metabolic abnormalities ranging from simple hepatic steatosis (accumulation of neutral lipid) to development of steatotic lesions, steatohepatitis, and cirrhosis. NAFLD is extremely prevalent in obese individuals and with the epidemic of obesity; nonalcoholic steatohepatitis (NASH) has become the most common cause of liver disease in the developed world. NASH is rapidly emerging as a prominent cause of liver failure and transplantation. Moreover, hepatic steatosis is tightly linked to risk of developing insulin resistance, diabetes, and cardiovascular disease. Abnormalities in hepatic lipid metabolism are part and parcel of the development of NAFLD and human genetic studies and work conducted in experimentally tractable systems have identified a number of enzymes involved in fat synthesis and degradation that are linked to NAFLD susceptibility as well as progression to NASH. The goal of this review is to summarize the current state of our knowledge on these pathways and focus on how they contribute to etiology of NAFLD and related metabolic diseases.